Desempenho de híbridos intraespecíficos de Brachiaria decumbens desenvolvidos por seleção recorrente recíproca - Matias, Filipe Inácio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The forage market has a demand for new cultivars of Brachiaria decumbens with superior agronomic performance and nutritional value. This demand encourages the pasture species improvement program. Therefore, it is necessary to select superior sexual genotypes of Brachiaria decumbens for the recombination in projects of reciprocal recurrent selection as a source of variability for the program and for the formation of a base population for selection. These genotypes can be used, for example, in the reciprocal recombination in recurrent selection schemes which in turn depend on the performance of ther progenies. These progenies are obtained from a cross with an apomictic tester genotype. The objective of this study was to estimate genetic parameters and genetic correlations for agronomic traits and nutritional value in intraspecific hybrids of B. decumbens. Furthermore, it aimed at comparing different indices for the selection of the best hybrids and genetic gain with different intensities of selection, as well as verifying the multivariate pattern of the progenies using a principal component analysis. For that, a population of 1,415 hybrids was evaluated in field plots at Embrapa Beef Cattle in Campo Grande/MS/Brazil, with seven cuts, estimating: field green weight (PVC); total dry matter (MST); speed of regrowth (VEL); tiller regrowth density (DEN); regrowth ability (REB); crude protein (CP); in vitro organic matter digestibility (DIV); neutral detergent fiber (NDF) and lignin (LIG). The statistical analyses were conducted using the mixed models methodology and principal component methodology. The presence of genetic variability for all characters assessed were detected and estimates of heritability of medium to high magnitude, indicating the possibility of gains with selection. Significant associations were observed between PVC and MST (0.99), MST and VEL (0.81), MST and DIV (-0.71), MST and LIG (0.71) and PB and DIV (0.70), indicating ...

O mercado forrageiro possui uma demanda por novas cultivares de Brachiaria decumbens que apresentem diferenciais quanto ao desempenho agronômico e valor nutritivo. Essa demanda impulsiona o surgimento de programas de melhoramento da espécie voltado para o desenvolvimento de cultivares. Para isso, é necessário à seleção de genótipos sexuais superiores de Brachiaria decumbens como fonte de variabilidade para o programa e formação da população base para recombinação, estes genótipos podem ser usados, por exemplo, na recombinação em esquemas de seleção recorrente reciproca que por sua vez é dependente do desempenho de suas progênies obtidas em cruzamentos com um genótipo apomítico testador. Assim, o objetivo deste trabalho foi estimar parâmetros genéticos e correlações genéticas para características agronômicas e de valor nutritivo em híbridos intraespecíficos de Brachiaria decumbens e comparar diferentes índices para a seleção dos melhores genitores e os ganhos obtidos com diferentes intensidades de seleção, bem como verificar o padrão multivariado das progênies por meio de análise de componentes principais. Para isso, uma população de 1.415 híbridos foi avaliada em campo experimental na Embrapa Gado de Corte em Campo Grande/MS/Brasil, durante sete cortes, para as características: peso verde de campo (PVC); matéria seca total (MST); velocidade de rebrota (VEL); densidade de perfilhos rebrotados (DEN); capacidade de rebrota (REB); proteína bruta (PB); digestibilidade in vitro da matéria orgânica (DIV); fibra em detergente neutro (FDN) e lignina (LIG). Avaliações complementares em casa de vegetação para definição de resistência as cigarrinhas das pastagens estão em andamento. As análises estatísticas foram realizadas utilizando a metodologia de modelos mistos e componentes principais. Evidenciou-se a presença de variabilidade genética para todos os caracteres avaliados e estimativas ...
Keywords: Brachiaria decumbens; Plantas forrageiras; Seleção de plantas - Melhoramento genetico; Desempenho; Genetica vegetal; Plant-breeding